Aspectos bioquímicos e ultraestruturais da maturação oocitária - Crocomo, Letícia Ferrari [UNESP] (2011)
The oocyte maturation is a crucial and limiting step for the in vitro embryo production, since the development potential of oocytes and embryos is directly related to proper nuclear and cytoplasmic maturation. The arrest, resumption and progression of meiotic divisions as well as molecular and structural changes are fundamental for the oocyte to complete the processes of maturation and fertilization, and sustain the early stages of embryonic development. These events involve a complex interaction between second messengers, protein kinases and phosphatases, which have not yet been fully clarified. The oocyte maturation in vitro, however, differs in certain aspects from that observed in vivo. So, the elucidation of the action mechanisms of several molecules involved in regulating oocyte maturation process is essential to scientific and biotechnological progress.